2011
DOI: 10.1007/s00425-011-1396-x
|View full text |Cite
|
Sign up to set email alerts
|

Anoxia-induced elevation of cytosolic Ca2+ concentration depends on different Ca2+ sources in rice and wheat protoplasts

Abstract: The anoxia-dependent elevation of cytosolic Ca(2+) concentration, [Ca(2+)](cyt), was investigated in plants differing in tolerance to hypoxia. The [Ca(2+)](cyt) was measured by fluorescence microscopy in single protoplasts loaded with the calcium-fluoroprobe Fura 2-AM. Imposition of anoxia led to a fast (within 3 min) significant elevation of [Ca(2+)](cyt) in rice leaf protoplasts. A tenfold drop in the external Ca(2+) concentration (to 0.1 mM) resulted in considerable decrease of the [Ca(2+)](cyt) shift. Rice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 41 publications
1
52
0
Order By: Relevance
“…For example, when challenged by anoxia, root protoplasts from hypoxia-tolerant rice display a greater [Ca 2+ ] cyt signature than hypoxia-intolerant wheat root protoplasts (Yemelyanov et al, 2011). The location of the Ca 2+ influx also varies; use of pharmacological blockers showed that the rice signature was generated by both PM influx and store release whilst wheat appeared to rely solely on stores (Yemelyanov et al, 2011). The types of Ca 2+ channels mediating the [Ca 2+ ] cyt increase have yet to be identified in any species.…”
Section: Mechanistic Basis Of [Ca2+]cyt Response To O2 Deficiency Remmentioning
confidence: 99%
“…For example, when challenged by anoxia, root protoplasts from hypoxia-tolerant rice display a greater [Ca 2+ ] cyt signature than hypoxia-intolerant wheat root protoplasts (Yemelyanov et al, 2011). The location of the Ca 2+ influx also varies; use of pharmacological blockers showed that the rice signature was generated by both PM influx and store release whilst wheat appeared to rely solely on stores (Yemelyanov et al, 2011). The types of Ca 2+ channels mediating the [Ca 2+ ] cyt increase have yet to be identified in any species.…”
Section: Mechanistic Basis Of [Ca2+]cyt Response To O2 Deficiency Remmentioning
confidence: 99%
“…Ca 2+ release from mitochondria may rather represent a hallmark of cellular energy crisis and loss of homeostasis than contribute to a specific signal. Yet, the cytosolic increase in Ca 2+ that has been consistently observed at hypoxia appears to be conserved throughout plants and chemical suppression hampers transcriptional induction of hypoxia-responsive genes such as ALCOHOL DEHYDROGENASE (Subbaiah et al, 1994;Sedbrook et al, 1996;Yemelyanov et al, 2011). The mechanism by which Ca 2+ fluxes modulate nuclear transcription is currently unknown.…”
Section: +mentioning
confidence: 99%
“…The involvement of calcium in hypoxia responses has been observed in many plants such as rice, wheat, and cucumber [10, 11]. This hypoxia-mediated elevation of Ca 2+ is fundamental for the activation of genes and synthesis of proteins required for acclimation responses at the cellular, tissue, and organismal levels [6, 12].…”
Section: Introductionmentioning
confidence: 99%